Hannah Arendt, Little Rock et la question de la neutralité scolaire - Michel Fabre (Éducation et Socialisation)
Ministerial circulars call not only for awareness-raising, but for a real “youth mobilisation” against global warming. These recommendations concern the neutrality of the school space within the republican framework. In order to depart from recurring debates in France, we propose here to take a detour through America, with the Little Rock affair and the Hannah Arendt’s paper about claims of the State to initiate the process of social desegregation by ordering public high schools to integrate black students. But engaging youth in adults political struggles, it is not betraying education ?Yet many tensions into Arendt's political philosophy suggest resting the problem of school neutrality in a less radical way when the subject concerns preservation of life, that is a necessary, although insufficient, condition of education. But, on the other hand, what to think mobilizing students by inculcating "good practices" without promoting reflection ? In short, if the school, as an institution, is to serve as a relay for public policies, how should it perform the role assigned to it ? Shouldn't youth mobilization take other forms than enrollment ?